Hypermethylation of the Promoter of miR-338-5p Mediates Aberrant Expression of ETS-1 and Is Correlated With Disease Severity Of Astrocytoma Patients - Wang, Junping; Huo, Cheng; Yin, Jinzhu; Tian, Lixia; Ma, Lili; Wang, Dongsheng (Frontiers in Oncology, 2021)
The pro-oncogene ETS-1 (E26 transformation-specific sequence 1) is a key regulator of the proliferation and invasion of cancer cells. The present work examined the correlation of the aberrant expression of ETS-1 with histological or clinical classification of astrocytoma: grade I (pilocytic astrocytoma), grade II (diffuse astrocytoma), grade III (anaplastic astrocytoma), and grade IV (glioblastoma multiforme). MicroRNA, miR-338-5p, was predicted by an online tool (miRDB) to potentially target the 3’ untranslated region of ETS-1; this was confirmed by multi-assays, including western blot experiments or the point mutation of the targeting sites of miR-338-5p in ETS-1’s 3’untralation region (3’UTR). The expression of miR-338-5p was negatively associated with that of ETS-1 in astrocytoma, and deficiency of miR-338-5p would mediate aberrant expression of ETS-1 in astrocytoma. Mechanistically, hypermethylation of miR-338-5p by DNA methyltransferase 1 (DNMT1) resulted in repression of miR-338-5p expression and the aberrant expression of ETS-1. Knockdown or deactivation of DNMT1 decreased the methylation rate of the miR-338-5p promoter, increased the expression of miR-338-5p, and repressed the expression of ETS-1 in astrocytoma cell lines U251 and U87. These results indicate that hypermethylation of the miR-338-5p promoter by DNMT1 mediates the aberrant expression of ETS-1 related to disease severity of patients with astrocytoma.